2006
DOI: 10.1373/clinchem.2005.064758
|View full text |Cite
|
Sign up to set email alerts
|

Fast In Vivo Microextraction: A New Tool for Clinical Analysis

Abstract: Background:We sought to develop a technique with the potential to partly replace current methods of analysis based on blood draws. To achieve this goal, we developed an in vivo microextraction technique that is faster than conventional methods, interferes minimally with the investigated system, minimizes errors associated with sample preparation, and limits exposure to hazardous biological samples. Methods: Solid-phase microextraction devices based on hydrophilic polypyrrole and polyethylene glycol coatings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 25 publications
1
83
0
1
Order By: Relevance
“…They introduced SPME fibres directly into a catheter in the carotid artery. 21 Their results correlated well with those of a standard analytical method using protein precipitation of blood samples obtained at preselected time points.…”
Section: 22supporting
confidence: 53%
See 1 more Smart Citation
“…They introduced SPME fibres directly into a catheter in the carotid artery. 21 Their results correlated well with those of a standard analytical method using protein precipitation of blood samples obtained at preselected time points.…”
Section: 22supporting
confidence: 53%
“…This validation of the SPME extraction technique for TXA results in adding another medication to the long list of analytes that have been investigated previously. 2,[18][19][20][21] It demonstrates potential of this analytical method to be applied for measurements of other agents of interest in clinical medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Prof. Pawliszyn`s group is the pioneer of in-vivo microextraction that solves this shortcoming [20]. As the name well indicates, this approach consists on the integration of sampling and microextraction and presents the following advantages: a) is faster than con-ventional approaches; b) minimizes error associated to sample treatment and c) minimizes the error associated to sample storage since the analysis is performed after the in-vivo extraction [21]. In addition, the microextraction does not change the system equilibrium since the amount of extracted analyte is very low.…”
Section: In-vivo Microextractionmentioning
confidence: 99%
“…12,13 Recently, the feasibility of the method was also shown for global screening purposes. [14][15][16][17] The main advantages of in vivo SPME, being a low invasive and nondisturbing method to the system under study, were demonstrated for pharmacokinetics and metabolomics in blood, [18][19][20][21][22][23] whereas in vivo tissue analyses were conducted for analysis of pharmaceuticals in living fish. 24,25 In addition, with the SPME technique, blood sampling can be performed directly from a vein by using a hypodermic needle-assembled SPME probe (Figure 1) or by insertion of the probe to the vein through the i.v.…”
mentioning
confidence: 99%
“…In addition, to control blood flow through the interface and increase the rate of extraction, a syringe or pump can be connected to the interface. [19][20][21][22][23] For tissue sampling, the SPME fiber can be placed in the studied tissue either by using the needleassembled device, as it is proposed in this work, or by using specially designed tissue samplers, as reported for fish muscle sampling. 25 In order to provide fully quantitative results, a Figure 1 The SPME probe with no assembly (a) and assembled in hypodermic needle (b, c).…”
mentioning
confidence: 99%